Functionalization of Carbon and Silica Gel by Phosphoric Acid - A.M. Puziy; O.I. Poddubnaya; B. Gawdzik; M. Sobiesiak; M.M. Tsyba (Adsorption Science & Technology)
Functionalization of polymer-based carbon (SCS-3) and silica gel (SG60) by phosphoric acid at 800°C was investigated. It was shown that heat treatment of carbon and silica gel in the presence of phosphoric acid at 800°C provides a way of functionalizing materials with phosphorus-containing surface groups. Functionalization of the finished carbon occurs as a surface reaction while destruction of the silica gel structure was observed. Functionalization with phosphoric acid creates new acid surface groups — phosphorus-containing and oxygen-containing in the case of carbon and only phosphorus-containing in the case of silica gel. Enhancement of the amount of acid surface groups by functionalization improves the metal-ion binding properties of both carbon and silica gel.